Synthesis of some novel pyrazolo[3,4-d]pyrimidine derivatives - Campos, Ana M. F. Oliveira (2007)
Reaction of ethyl imidates derived from N-aryl-5-amino-4-cyanopyrazoles with amines or arylhydrazines gave only 4-substituted pyrazolo[3,4-d]pyrimidines, resulting from cyclization followed by Dimroth rearrangement. From the reaction with arylhydrazines, a mixture of the hydrazines and their oxidized forms, the azo products, was obtained. This was proven by an independent synthesis starting from the corresponding 4-chloropyrazolo[3,4-d]pyrimidines as starting material. The structures of the compounds obtained were confirmed by mass spectrometry, 1H and 13C NMR.